Performance of Hungarian firms: Are apprentices an asset or a liability? Evidence from a unique matched employer-employee dataset - Sofie Cabus; Eszter Nagy (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2017)
Hungarian legislation provides firms with financial incentives to train apprentices from vocational training schools. In line with these incentives, it is observed that firms increasingly train apprentices over the period 2003-2011, in particular, in the sectors manufacturing, construction, wholesale and retail and hotels and restaurants. However, at the same time, it is observed that firms decreasingly retain the trained apprentices in these four sectors. This finding leads to the hypothesis that apprentices are not profitable in the long run. The formulated hypothesis is known in the previous literature as the 'substitution strategy'. This recruiting strategy is particularly observed among firms that replace their low-skilled labour with apprentices in order to reduce the cost of wages. For these firms it is not beneficial to hire an apprentice after accomplishing his training, because then he becomes a low-skilled worker paid at higher wages. This paper investigates the effect of the share of days worked by apprentices on productivity and gross profits of Hungarian firms by using a unique matched employer-employee dataset. Different approaches that allow us to estimate the effect are discussed among which fixed effects first-difference models and system GMM. The results indicate that apprentices decrease productivity and gross profits of Hungarian firms. These negative effects on firm performance were more prominent and robust before (2003-2007) than after the financial crisis (2008-2011).
Keywords: I21; J24; L25; 330; apprenticeship training; firm performance; panel data